A feasibility of computational drug screening for Fuchs endothelial corneal dystrophy - Oka, Itsuki; Toyokawa, Yoshiaki; Imai, Kouta; Nakagawa, Tatsuya; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko; Okumura, Naoki (Scientific Reports, 2025)
Fuchs endothelial corneal dystrophy (FECD) remains a leading cause of corneal blindness globally, with corneal transplantation being the primary treatment. FECD is characterized by the formation of guttae, extracellular matrix (ECM) deposits beneath the corneal endothelium, and progressive endothelial cell loss. These pathological changes cause visual deterioration through light scattering by guttae and corneal edema due to endothelial cell loss. However, limitations such as donor shortage and graft failure necessitate alternative therapeutic approaches. We employed computational drug screening using three platforms (L1000FWD, L1000CDS2, and SigCom LINCS) to identify compounds capable of normalizing FECD-associated differentially expressed genes (DEGs). Analysis of transcriptome data from FECD patients with TCF4trinucleotide repeat expansion identified 706 upregulated and 962 downregulated genes. The screening platforms identified 200, 35, and 76 compounds through L1000FWD, L1000CDS2, and SigCom LINCS, respectively, with five compounds commonly predicted across all platforms. Among these, LDN193189 and cercosporin were selected for further evaluation based on availability and lack of cytotoxicity. Both compounds significantly decreased the expression of ECM-related genes (FN1, MATN3, BGN, and LTBP2) in FECD cell models and suppressed TGF-β-induced fibronectin expression. Additionally, both compounds reduced aggresome formation to normal control levels, suggesting protection against endoplasmic reticulum stress-induced cell death. This study demonstrates the feasibility of computational drug screening for identifying therapeutic candidates for FECD, with LDN193189 and cercosporin showing promise in normalizing FECD-associated pathological changes.
CRIS-Team Scopus Importer:2025-05-09

Association of rs613872 and Trinucleotide Repeat Expansion in the TCF4 Gene of German Patients With Fuchs Endothelial Corneal Dystrophy - Okumura, Naoki; Hayashi, Ryousuke; Nakano, Masakazu; Tashiro, Kei; Yoshii, Kengo; Aleff, Ross; Butz, Malinda; Highsmith, Edward W.; Wieben, Eric D.; Fautsch, Michael P.; Baratz, Keith H.; Komori, Yuya; et al. (Cornea, 2019)
PURPOSE: To investigate single nucleotide polymorphisms (SNPs) and trinucleotide repeat (TNR) expansion in the transcription factor 4 (TCF4) gene in a large cohort of German patients with Fuchs endothelial corneal dystrophy (FECD). METHODS: Genomic DNA was obtained from 398 patients with FECD and from 58 non-FECD controls. Thirty-seven previously reported SNPs were evaluated by genotyping. The 398 FECD samples were analyzed for TNR expansions by short tandem repeat assays and Southern blotting. The possible associations between the TNR length and clinical parameters (age, sex, visual acuity, and central corneal thickness) were analyzed in 132 patients. RESULTS: The SNPs in COL8A2, TCF8, LOXHD1, and AGBL1 showed no heterogeneity in 36 cases, although SLCA411 showed 3 nonsense mutations. SNPs were detected for TCF4 (rs613872, rs2123392, rs17089887, rs1452787, and rs1348047), but only rs613872 showed a significant association with FECD (P = 9.93 × 10). Overall, 315/398 (79%) patients harbored TNR lengths >50, whereas no non-FECD controls harbored TNR lengths >50. The TCF4 SNP rs613872 genotype was TT: 39 (67%), TG: 18 (31%), and GG: 1 (2%) in non-FECD controls; TT: 39 (47%), TG: 38 (46%), and GG: 6 (7%) in FECD cases harboring TNR <50; and TT: 23 (8%), TG: 224 (79%), and GG: 38 (13%) in FECD cases harboring TNR >50 (P = 2.93 × 10). No significant association was detected between the TNR length and clinical parameters. CONCLUSIONS: Our large German cohort demonstrated a significant association between the risk allele G in rs613872 and FECD, irrespective of TNR expansion, although this risk allele was more frequent in FECD cases with TNR expansion than without.
CRIS-Team Scopus Importer:2019-06-25

Characterisation of ectasia after penetrating keratoplasty in keratoconus eyes using anterior segment optical coherence tomography - Weller, Julia; Hübner, Lisa; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2023)
Background/aims: Ectasia of the cornea can occur decades after penetrating keratoplasty (PK), especially in keratoconus eyes. The purpose of this study was to characterise ectasia after PK by morphological findings in anterior segment optical coherence tomography (AS-OCT). Methods: In this retrospective, single-centre case series, 50 eyes of 32 patients with a history of PK at an average of 25±10 years earlier were included. The eyes were classified either as ectatic (n=35) or as non-ectatic (n=15). The main parameters included central corneal thickness (CCT), lowest corneal thickness at the interface (LCTI), anterior chamber depth, graft-host interface angle at the thinnest point and host cornea-iris angle. Furthermore, steep and flat keratometry readings obtained by AS-OCT (CASIA-2, Tomey) and Scheimpflug tomography (Pentacam, Oculus) were assessed. OCT findings were correlated with clinical grading of ectasia. Results: There was a highly significant difference in LCTI, graft-host interface angle and anterior chamber depth (in pseudophakic eyes) between the groups. The ratio calculated by the quotient of LCTI divided by CCT was significantly lower in ectatic than non-ectatic eyes (p<0.001). In eyes with an LCTI/CCT ratio of ≤0.7, the OR for the occurrence of a clinical detectable ectasia was 2.4 (CI 1.5 to 3.7). Steep keratometry values were significantly higher in ectatic eyes. Conclusion: AS-OCT is a helpful tool to recognise and quantify ectasia in post-PK eyes objectively.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Cornea; Imaging; Treatment Surgery

Comprehensive analysis of splicing variants in corneal endothelial cells of patients with Fuchs endothelial corneal dystrophy - Yuasa, Taichi; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko; Okumura, Naoki (Scientific Reports, 2025)
Trinucleotide repeat (TNR) expansion in the transcription factor 4 (TCF4) gene represents the most prevalent genetic risk factor for Fuchs endothelial corneal dystrophy (FECD) and may cause dysfunction of splicing regulators. We investigated differential alternative splicing (DAS) events in corneal endothelial cells (CECs) from FECD patients with and without TCF4 TNR expansion through RNA-Seq analysis. We identified distinct splicing profiles among control subjects, FECD patients with TNR expansion, and FECD patients without TNR expansion. Skipped Exon events constituted approximately 50% of all DAS events across all comparisons, with the remaining events distributed among alternative 3’ splice site, alternative 5’ splice site, mutually exclusive exon, and retained intron categories. Motif analysis in FECD patients with TNR expansion revealed several RNA-binding proteins, including MBNL1, as potential regulators of these splicing alterations. Computational analysis demonstrated that 34% of Skipped Exon events in the TNR expansion group significantly impacted protein structure. This comprehensive analysis revealed distinct alternative splicing signatures in FECD, particularly in cases with TNR expansion, suggesting a crucial role for aberrant splicing in FECD pathogenesis.
CRIS-Team Scopus Importer:2025-05-09

Comprehensive identification of dysregulated extracellular matrix molecules in the corneal endothelium of patients with Fuchs endothelial corneal dystrophy - Inagaki, Soichiro; Vaitinadapoule, Hanielle; Yuasa, Taichi; Nakagawa, Tatsuya; Ikegawa, Masaya; Toyama, Yumiko; Nirasawa, Takashi; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; et al. (Scientific Reports, 2025)
Fuchs endothelial corneal dystrophy (FECD) is a bilateral, progressive corneal endothelial disease characterized by the formation of extracellular matrix (ECM) excrescences called guttae. This study integrated proteomic and transcriptomic analyses to elucidate the molecular composition and spatial organization of ECM proteins in the Descemet membrane (DM) of FECD patients. Through shotgun proteomics of FECD-derived DM specimens and RNA sequencing data from FECD (n = 10) and control (n = 7) corneal endothelial cells, we identified 19 significantly upregulated molecules in FECD, including 13 ECM-related proteins. Gene Ontology and Reactome analyses revealed ECM-related pathways as central to FECD pathology. Immunofluorescence analyses of flat-mounted and cross-sectional specimens from FECD patients undergoing Descemet membrane endothelial keratoplasty (DMEK) and controls demonstrated distinct spatial patterns for six ECM proteins. Fibronectin and collagen VI α1 were detected on the outer surfaces of guttae, matrilin-3 and biglycan localized around guttae, while LTBP2 and tenascin were strongly associated with the posterior fibrillar layer (PFL). The peripheral corneal regions predominantly exhibited scattered guttae, whereas the central region displayed buried guttae encapsulated by ECM deposition. This study comprehensively examined ECM protein expression patterns, revealing distinct spatial distributions across guttae, PFL, and surrounding DM regions. These findings suggest that clinical assessments should incorporate both guttae confluence and the presence of ECM-rich PFL to achieve a more comprehensive understanding of FECD progression, thereby informing more accurate staging and optimal surgical planning.
CRIS-Team Scopus Importer:2025-05-09

Deep neural network by transfer learning for the analysis of guttae in the patients with Fuchs endothelial corneal dystrophy - Narimoto, Kaito; Okumura, Naoki; Yamada, Shohei; Okamura, Kengo; Izumi, Ayaka; Tourtas, Theofilos; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Descemet membrane endothelial keratoplasty: analysis of clinical outcomes of patients with 8-10 years follow-up - Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (International Ophthalmology, 2022)
Purpose This study aimed to evaluate the clinical outcomes up to 10 years after Descemet membrane endothelial keratoplasty (DMEK). Methods In this retrospective, consecutive, single-center case series the medical files of eyes which have received DMEK between 2009 and 2012 for the treatment of endothelial dysfunction was evaluated regarding follow-up time and clinical outcomes. Annual examinations of best-corrected visual acuity (BCVA), endothelial cell density (ECD), central corneal thickness (CCT) of 66 eyes which fulfilled the criterion of a minimum of 8 years follow-up were analyzed. Results BCVA improved from 0.55 +/- 0.37 logMAR (n = 54) to 0.15 +/- 0.11 (n = 47) in eyes without ocular comorbidities one year after DMEK (p < 0.001), and remained stable up to 10 years after DMEK. Mean ECD decreased to 744 +/- 207 cells/mm(2) (n = 39) after 9 years, and to 729 +/- 167 cells/mm(2) (n = 21) after 10 years, respectively. CCT decreased from 650 +/- 67 mu m before DMEK to 525 +/- 40 mu m (n = 56) after 1 year, increasing slowly to 563 +/- 40 mu m (n = 39) after 9 years, and to 570 +/- 42 mu m (n = 21) after 10 years, respectively. Graft failure occurred in 4 of 66 eyes after year 8. These 4 eyes required repeat DMEK after 101-127 months. Conclusion This study shows the long-term outcomes in a small subset of DMEK grafts. Visual acuity remained stable in spite of slowly increasing corneal thickness and diminishing endothelial cell density during the 10-year period after DMEK.
CRIS-Team WoS Importer:2022-01-14

Differences in Guttae Ultramorphology in Relation to Visual Function in Fuchs Endothelial Corneal Dystrophy - Weller, Julia; Bennemann, Maximilian; Tourtas, Theofilos; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula (Cornea, 2024)
PURPOSE: The purpose of this study was to investigate the differences in guttae ultramorphology and their relation to visual function in eyes with Fuchs endothelial corneal dystrophy (FECD). METHODS: Thirty FECD eyes without ocular comorbidities were included. Visual functional parameters (best-corrected visual acuity with high-contrast and low-contrast letters and contrast sensitivity/LogCS) and corneal morphology measured with Scheimpflug tomography (Pentacam) were assessed. The surgically removed Descemet membranes were examined by light and transmission electron microscopy. RESULTS: Preoperative mean best-corrected visual acuity (logarithm of the minimum angle of resolution) was 0.52 ± 0.18, LogCS 0.96 ± 0.21 and central corneal thickness 640 ± 55 μm. All eyes had signs of subclinical corneal edema in Scheimpflug tomography; clinically visible corneal edema was present in 40% of eyes. Histological findings included a posterior fibrillar zone (PFZ) in 10 specimens (33%) and abnormal collagen depositions in Descemet membranes in 14 specimens (47%). Guttae buried within the PFZ were present only in eyes with clinically visible edema (n = 4, 13%). There was no difference in visual function results and tomography parameters between eyes with and without PFZ or between protruding guttae and guttae embedded in a PFZ, respectively. CONCLUSIONS: Guttae morphology and density were not correlated with visual functional parameters. Guttae buried in a PFZ occurred only in eyes with clinically manifest edema, and thereby, they are an ultramorphological sign for advanced FECD. Subclinical edema was present in all eyes and might be more relevant for quality of vision than guttae ultramorphology.
CRIS-Team Scopus Importer:2024-10-11

Drug- and Cell-Type-Specific Effects of ROCK Inhibitors as a Potential Cause of Reticular Corneal Epithelial Edema - Schlötzer-Schrehardt, Ursula; Gießl, Andreas; Zenkel, Matthias; Bartsch, Alexander; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; Kruse, Friedrich (Cells, 2025)
Rho-associated kinase (ROCK) inhibitors have gained popularity as novel treatment options in the management of glaucoma and corneal endothelial disorders. Among the various ocular side effects, reticular corneal epithelial edema has been most frequently reported, mainly after treatment with netarsudil. To explain the potential mechanisms, we comparatively analyzed the effects of ripasudil and netarsudil on corneal endothelial and epithelial function in vitro. Primary human corneal endothelial and epithelial cells were incubated with netarsudil dihydrochloride and ripasudil hydrochloride dihydrate for up to 7 days. Gene and protein expression analyses were performed by real-time PCR and immunocytochemistry. Functional assays assessed the cell migration, proliferation, viability, Na+/K+-ATPase activity, transcellular electrical resistance, and FITC–dextran permeability. Reticular bullous corneal epithelial edema was observed in a patient following netarsudil 0.02%/latanoprost 0.005% ophthalmic solution (Roclanda®) for elevated intraocular pressure. In the subsequent laboratory analyses, both netarsudil and ripasudil were found to improve the corneal endothelial pump and barrier function, but they showed differential effects on corneal epithelial cells. Whereas ripasudil improved the epithelial barrier function by upregulating major components of the tight and adherens junctions and reducing paracellular permeability, netarsudil had no or even adverse effects on the epithelial barrier properties by downregulating the expression levels of cell-junction-associated genes. The expression changes normalized after discontinuation of ROCK inhibitors. The findings support the concept that ROCK inhibitors can act as a double-edged sword by having beneficial effects on corneal endothelial cells and adverse effects on epithelial cells.
CRIS-Team Scopus Importer:2025-03-14
Keywords: corneal endothelium; corneal epithelium; honeycomb epithelial edema; netarsudil; reticular bullous corneal epithelial edema; Rho kinase inhibitor; ripasudil; ROCK inhibitor

Dysregulation of the TCF4 Isoform in Corneal Endothelial Cells of Patients With Fuchs Endothelial Corneal Dystrophy - Honda, Tetsuro; Nakagawa, Tatsuya; Yuasa, Taichi; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Yamamoto, Koji; Koizumi, Noriko; Okumura, Naoki (Investigative Ophthalmology & Visual Science, 2024)
PURPOSE. This study evaluated the dysregulation of TCF4 isoforms and differential exon usage (DEU) in corneal endothelial cells (CECs) of Fuchs endothelial corneal dystrophy (FECD) with or without trinucleotide repeat (TNR) expansion in the intron region of the TCF4 gene. METHODS. Three RNA-Seq datasets of CECs (our own and two other previously published datasets) derived from non-FECD control and FECD subjects were analyzed to identify TCF4 isoforms and DEU events dysregulated in FECD by comparing control subjects to those with FECD with TNR expansion and FECD without TNR expansion. RESULTS. Our RNA-Seq data demonstrated upregulation of three TCF4 isoforms and downregulation of two isoforms in FECD without TNR expansion compared to the controls. In FECD with TNR expansion, one isoform was upregulated and one isoform was downregulated compared to the control. Additional analysis using two other datasets identified that the TCF4-277 isoform was upregulated in common in all three datasets in FECD with TNR expansion, whereas no isoform was dysregulated in FECD without TNR expansion. DEU analysis showed that one exon (E174) upstream of the TNR, which only encompassed TCF4-277, was upregulated in common in all three datasets, whereas eight exons downstream of the TNR were downregulated in common in all three datasets in FECD with TNR expansion. CONCLUSIONS. This study identified TCF4-277 as a dysregulated isoform in FECD with TNR expansion, suggesting a potential contribution of TCF4-277 to FECD pathophysiology.
CRIS-Team Scopus Importer:2024-06-28
Keywords: differential exon usage; fuchs endothelial corneal dystrophy; isoform; RNA-Seq; TCF4

Influence of corneal guttae and nuclear cataract on contrast sensitivity - Augustin, Victor A.; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (British Journal of Ophthalmology, 2020)
AIMS: To evaluate the contrast sensitivity in patients with nuclear cataract and corneal guttae compared to patients with nuclear cataract without guttae. METHODS: In this retrospective, single-centre case series, 50 eyes of 50 patients fulfilling the inclusion criteria were enrolled. Patients with corneal guttae and nuclear cataract (n=25, study group) underwent triple Descemet membrane endothelial keratoplasty (DMEK). Patients with nuclear cataract and healthy corneas underwent cataract surgery (n=25, control group). Inclusion criteria were preoperative best-corrected visual acuity ≥20/40, no corneal oedema and similar lens opacity (nuclear opalescence 2.0-2.9). Outcome measures included MARS letter and OPTEC 6500P contrast sensitivity test, corneal volume, central corneal thickness and anterior and posterior corneal densitometry. RESULTS: Preoperative MARS letter and OPTEC 6500P contrast sensitivity was significantly worse in the study group (MARS: p<0.001; OPTEC 6500P: p<0.007 at low spatial frequencies in daylight with and without glare and nightlight without glare). After surgery, there was no significant difference in MARS letter contrast sensitivity between groups (p=0.225). OPTEC 6500P contrast sensitivity remained significantly lower in the study group in daylight and nightlight with and without glare at most spatial frequencies (p<0.01) postoperatively. Preoperative and postoperative corneal volume, central corneal thickness and anterior corneal densitometry were equal in both groups (p>0.05). Posterior densitometry was significantly higher in the study group than in the control group preoperatively (p<0.001) but turned into equal values postoperatively (p=0.07). CONCLUSIONS: Corneal guttae cause an additional significant decrease in contrast sensitivity in eyes with nuclear cataract. This is in favour of performing a triple DMEK even in eyes with a visual acuity of ≥20/40.
CRIS-Team Scopus Importer:2020-10-09

Involvement of TGF-β signaling pathway-associated genes in the corneal endothelium of patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Honda, Tetsuro; Inagaki, Soichiro; Yuasa, Taichi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Aouimeur, Ines; Vaitinadapoule, Hanielle; Travers, Gauthier; He, Zhiguo; Gain, Philippe; et al. (Experimental Eye Research, 2025)
This study investigated the involvement of TGF-β signaling pathway-associated genes in the pathogenesis of Fuchs endothelial corneal dystrophy (FECD). The RNA-sequencing analysis of corneal endothelial cells (CECs) from FECD patients revealed significant alterations in multiple TGF-β superfamily genes, with 9 genes upregulated (including BMP6, GDF5, and TGF-β2) and 10 genes downregulated (including BMP2, NOG, and INHBA) compared to controls. Quantitative PCR validation confirmed the elevated expression of GDF5 (3.35-fold in non-expanded and 7.66-fold in expanded TCF4), TGF-β2 (6.17-fold and 11.5-fold), and TGF-β1 (1.78-fold and 1.58-fold) in FECD patients with and without TCF4 trinucleotide repeat expansion. Ex-vivo experiments using donor corneas demonstrated that TGF-β2 stimulation significantly increased the expression of extracellular matrix (ECM) components associated with guttae formation, including fibronectin, types I and VI collagens, and other matrix proteins. Immunofluorescence confirmed increased fibronectin protein expression in the corneal endothelium following TGF-β1 or TGF-β2 treatment. This study provides the first comprehensive analysis of TGF-β superfamily involvement in FECD and suggests that GDF5, found to be upregulated in FECD, may contribute to the disease process. These findings further indicate that dysregulation of TGF-β signaling pathways drives the characteristic ECM accumulation in FECD, potentially offering new therapeutic targets for this progressive corneal disease involving fibrosis-related alterations. Future research is warranted to clarify GDF5's specific role and mechanistic impact on FECD pathogenesis.
CRIS-Team Scopus Importer:2025-04-01
Keywords: FECD; Fuchs endothelial corneal dystrophy; GDF5; RNA-Seq; TGF-β

Keratomalacia and corneal perforation in vitamin A deficiency: Anterior-segment optical-coherence-tomography and histological findings - Weller, Julia; Tourtas, Theofilos; Kruse, Friedrich (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To describe the histological findings and results of anterior-segment optical-coherence-tomography (AS-OCT) in patients with severe keratomalacia and corneal perforation due to vitamin-A deficiency (VAD). Observations: Four patients (3 female, 1 male) with moderate to severe VAD were included in this single-center case series. Keratomalacia/corneal perforation was diagnosed by slit-lamp examination. The findings were documented using photographs and AS-OCT imaging (CASIA-2, Tomey corporation, Nagoya, Japan). Ocular and general medical findings including causes of VAD are reported. VAD was severe (<20 ng/ml) in two patients with chronic alcoholism, and moderate (205/231 ng/ml) in two patients with cachexia. Corneal perforation occurred in 3 out of 4 patients. One patient had severe keratomalacia with impending perforation and massive conjunctival folds with Bitot's spots, which vanished soon after initiation of vitamin A supplementation. In three cases, corneal specimens obtained during anterior lamellar keratoplasty were assessed histologically by light-microcopy. The histological specimens showed massive epithelial thickening and a pronounced granular layer of the corneal epithelium. Conclusions and importance: Keratomalacia leading to corneal perforation is a rare, but possible complication also in countries with sufficient general food supply. The clinico-pathological correlation between AS-OCT and histological findings in patients with VAD is shown in this case series. Typical Bitot's spots were present only in one patient and can be visualized by AS-OCT.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Corneal perforation; Optical coherence tomography; Vitamin A deficiency

Management of Late Descemet's Membrane Detachment after Penetrating Keratoplasty in Keratoconus - Weller, Julia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos (Cornea, 2022)
Purpose:The purpose of this study was to describe the feasibility of Descemet membrane endothelial keratoplasty (DMEK) as a treatment modality for spontaneous detachment of DM (DMD) decades after penetrating keratoplasty (PK) for keratoconus.Methods:We describe the clinical characteristics and therapeutic surgical approach in 6 eyes of 5 patients with DMD. Clinical images, anterior segment optical coherence tomography scans, and histological findings are presented.Results:Mean age of patients at time of diagnosis was 60 years (range 56-66 years). Mean interval between PK and occurrence of DM detachment was 36 years (range 29-45 years). In 4 of 6 eyes, air injections into the anterior chamber were initially attempted to reattach DM to the stroma but without long-lasting effect. Two eyes underwent repeat PK because of pronounced ectasia after long-standing DMD and stromal scars. DMEK was performed successfully in 4 eyes leading to an increase in visual acuity and a reduction in central corneal thickness. Electron microscopy showed abnormal vacuolar inclusions and collagenous material in the posterior nonbanded layer and a separation of the anterior banded layer from the posterior nonbanded layer.Conclusions:This case series provides evidence that DMEK is a viable option in eyes with spontaneous DM detachment after PK. Visual outcome is limited by the persisting high astigmatism in the ectatic cornea. Illustrated by a small series of patients, the results of DMEK in this condition are presented and new findings about the pathophysiology are given.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Descemet membrane detachment; DMEK; keratoconus

Potential Functional Restoration of Corneal Endothelial Cells in Fuchs Endothelial Corneal Dystrophy by ROCK Inhibitor (Ripasudil) - Schlötzer-Schrehardt, Ursula; Zenkel, Matthias; Strunz, Maria; Gießl, Andreas; Schondorf, Hannah; da Silva, Heather; Schmidt, Gregory A.; Greiner, Mark A.; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; et al. (American Journal of Ophthalmology, 2021)
Purpose: Rho-associated kinase (ROCK) inhibitors have been successfully used as a rescue strategy in eyes that failed to clear after descemetorhexis without endothelial graft for treatment of Fuchs endothelial corneal dystrophy (FECD). The functional mechanisms by which ROCK inhibitors modulate corneal endothelial cell regeneration in FECD patients have, however, not been clarified. Here, we analyzed the effect of the ROCK inhibitor ripasudil on corneal endothelial cells of FECD patients and normal donors using ex vivo tissue and in vitro cellular models. Design: Experimental study: laboratory investigation. Methods: This institutional study used endothelial cell–Descemet membrane lamellae from FECD patients (n = 450) undergoing Descemet membrane endothelial keratoplasty (FECD ex vivo model), normal research-grade donor corneas (n = 30) after scraping off central endothelial cells (ex vivo wound healing model), normal donor corneas (n = 20) without endothelial injury, and immortalized cell lines (n = 3) generated from FECD patients (FECD in vitro model). Descemet membrane lamellae were dissected into halves and incubated for 24-72 hours in storage medium with or without a single dose of 30 μM ripasudil. The effects of ripasudil on expression of genes and proteins related to endothelial cell proliferation, migration, functionality, and endothelial-to-mesenchymal transition were analyzed and complemented by functional assays on FECD cell lines. Results: A single dose of ripasudil induced significant upregulation of genes and proteins related to cell cycle progression, cell-matrix adhesion and migration, as well as endothelial barrier and pump function up to 72 hours, whereas classical markers of endothelial-to-mesenchymal transition were downregulated in both FECD and normal specimens compared to unstimulated controls ex vivo. In addition to stimulation of proliferation and migration, ripasudil-induced changes in expression of functional signature genes could be also verified in FECD cell lines in vitro. Conclusions: These data support the concept that inhibition of ROCK signaling represents a potent tool in regenerative therapies in FECD patients through reactivation of cell proliferation and migration as well as restoration of endothelial pump and barrier function without inducing adverse phenotypic changes.
CRIS-Team Scopus Importer:2021-02-12

Proteomic analysis of TCF4 knock-out corneal endothelial cells derived from thepatients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Okumura, Naoki; Hanada, Naoya; Padmanabhan, Prema; Elchuri, Sailaja; Chatterjee, Amit; Janakiraman, Narayanan; Sathe, Gajanan; Ghose, Vivek; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; et al. (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-10-15

Refractive Outcomes After Descemet Membrane Endothelial Keratoplasty plus Cataract/Intraocular Lens Triple Procedure: A Fellow Eye Comparison - Augustin, Victor A.; Weller, Julia; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2021)
Purpose: Descemet membrane endothelial keratoplasty is often combined with phacoemulsification and intraocular lens implantation (DMEK + cataract/IOL triple procedure) in phakic patients. This procedure results in a refractive shift that is difficult to predict. The aim of this study was to evaluate the hypothesis that the refractive shift in the second eye follows the shift in the first eye. Methods: In this retrospective, single-center, consecutive case series, the refractive outcomes of 254 eyes of 127 patients who underwent DMEK + cataract/IOL triple procedure in both eyes for Fuchs endothelial corneal dystrophy have been analyzed. Main outcome measures were spherical equivalent outcome (shift calculations), best spectacle-corrected visual acuity, central corneal thickness, and posterior simulated keratometry. Results: The mean best spectacle-corrected visual acuity before surgery was 0.51 +/- 0.24 and increased to 0.19 +/- 0.15 (logMAR) after surgery (P < 0.001). After surgery, a mean hyperopic shift of 0.98 +/- 0.89 D was observed. The refractive shift was 1.03 +/- 0.93 D and 0.92 +/- 1.02 D, in the first and second eyes, respectively (P = 0.435). In a paired analysis, the mean difference of the refractive shift between the first and second eyes was 0.49 +/- 0.43 D. Conclusions: In our fellow eye comparison, the refractive shift after DMEK + cataract/IOL triple procedure in the second eye was comparable with the shift in the first eye. As a consequence, the refractive outcome of the first eye might serve as a reference for optimizing the refractive target in the second eye. Further studies investigating the influence of corneal parameters on refractive shift are needed for a more predictable lens power selection.
CRIS-Team WoS Importer:2021-11-26

RNA-Seq–based transcriptome analysis of corneal endothelial cells derived from patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Tokuda, Yuichi; Nakano, Masakazu; Komori, Yuya; Hanada, Naoya; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Tashiro, Kei; Koizumi, Noriko; Okumura, Naoki (Scientific Reports, 2023)
Fuchs endothelial corneal dystrophy (FECD) is the most common inherited corneal disease. Fibrillar focal excrescences called guttae and corneal edema due to corneal endothelial cell death result in progressive vision loss. Multiple genetic variants have been reported, but the pathogenesis of FECD is not fully understood. In this study, we used RNA-Seq to analyze differential gene expression in the corneal endothelium obtained from patients with FECD. Differential expression analysis of transcriptomic profiles revealed that expression of 2366 genes (1092 upregulated and 1274 downregulated genes) was significantly altered in the corneal endothelium of patients with FECD compared to healthy subjects. Gene ontology analysis demonstrated an enrichment of genes involved in extracellular matrix (ECM) organization, response to oxidative stress, and apoptotic signaling. Several pathway analyses consistently indicated the dysregulation of ECM-associated pathways. Our differential gene expression findings support the previously proposed underlying mechanisms, including oxidative stress and apoptosis of endothelial cells, as well as the phenotypic clinical FECD hallmark of ECM deposits. Further investigation focusing on differentially expressed genes related to these pathways might be beneficial for elucidating mechanisms and developing novel therapies.
CRIS-Team Scopus Importer:2023-06-30

RNA-Seq based transcriptome analysis of corneal endothelial cells derived from the patients with Fuchs endothelial corneal dystrophy - Nakagawa, Tatsuya; Okumura, Naoki; Komori, Yuya; Hanada, Naoya; Tokuda, Yuichi; Nakano, Masakazu; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Sex-Dependent Variations in Gene Expression in Corneal Endothelial Cells among Healthy Individuals and Patients with Fuchs Endothelial Corneal Dystrophy - Nakagawa, Tatsuya; Tateishi, Ayana; Tokuda, Yuichi; Nakano, Masakazu; Tashiro, Kei; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko (Cornea, 2025)
Purpose:Fuchs endothelial corneal dystrophy (FECD) displays a higher incidence in females than in males, yet the underlying mechanism remains unclear. This study aimed to elucidate sex-dependent differential gene expressions in corneal endothelial cells (CECs) from healthy non-FECD individuals and from patients with FECD.Methods:RNA-Seq data from CECs of non-FECD subjects (3 males, 4 females) and FECD subjects (5 males, 5 females) were analyzed to identify differentially expressed genes (DEGs) between the sexes. We used heatmaps and principal component analysis for expression pattern visualization and Gene Ontology analysis for functional categorization of DEGs.Results:Among the non-FECD subjects, we identified 341 DEGs - 143 upregulated and 198 downregulated - in females relative to males. For FECD subjects, 309 DEGs were discovered, with 215 upregulated and 94 downregulated in females compared with males. Heatmaps exhibited hierarchical clustering by sex, whereas principal component analysis delineated distinct male and female clusters in both non-FECD and FECD cohorts. Gene Ontology enrichment analysis linked the upregulated genes in non-FECD females to steroid hormone response, and downregulated ones to cyclin-dependent protein kinase activity. In females with FECD, upregulated genes were associated with immune responses and downregulated genes with peptide hormone binding.Conclusions:To our knowledge, these findings are the first to reveal distinct gene expression patterns in CECs between sexes. The observed variations suggest a potential genetic basis for the observed sex disparity in FECD prevalence. Further investigation is warranted to explore these associations and their implications for the pathogenesis of FECD.
CRIS-Team Scopus Importer:2025-01-31
Keywords: corneal endothelial cell; Fuchs endothelial corneal dystrophy; RNA sequencing; sex-biased gene

TCF4 expansion–associated loss of FN1 intron retention drives extracellular matrix accumulation in Fuchs endothelial corneal dystrophy - Inagaki, Soichiro; Yuasa, Taichi; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Koizumi, Noriko; Okumura, Naoki (Experimental Eye Research, 2025)
Fuchs endothelial corneal dystrophy (FECD), which is characterized by excessive extracellular matrix (ECM) accumulation and corneal endothelial cell degeneration, has trinucleotide repeat expansion in TCF4 as a major genetic risk factor. While aberrant splicing has been implicated in FECD pathogenesis, the mechanistic link between splicing abnormalities and disease-specific features remains unclear. Here, we investigated the intron retention (IR) patterns in corneal endothelial cells from FECD patients with TCF4 expansion. Initial RNA-Seq analysis using rMATS identified 486 upregulated and 89 downregulated IR events in expansion-positive FECD compared to controls. Subsequent analysis with the more stringent IRFinder algorithm revealed 10 upregulated IR events distributed across nine genes and, notably, 6 downregulated events exclusively localized within FN1, a major component of corneal guttae. While DEXSeq analysis showed reduced expression across FN1 gene regions in FECD samples, subsequent qPCR validation in an independent cohort demonstrated significantly elevated FN1 expression in both expansion-positive and expansion-negative FECD samples compared to controls. This paradoxical finding suggests that the loss of normal IR-mediated regulation may contribute to pathological FN1 overexpression in FECD. Gene ontology analysis of IR-associated genes revealed enrichment in RNA splicing and ECM-related pathways, supporting a role for IR in disease pathogenesis. Our findings reveal an association between TCF4 expansion and reduced FN1 intron retention, which correlates with ECM accumulation, suggesting a potential link between RNA processing alterations and hallmark features of FECD. These results suggest that targeting IR-mediated regulation could represent a therapeutic strategy for preventing disease progression.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Fuchs endothelial corneal dystrophy; Intron retention; RNA-Seq; Splicing

Therapeutic Potential of Emricasan, a Pan-Caspase Inhibitor, in Reducing Cell Death and Extracellular Matrix Accumulation in Fuchs Endothelial Corneal Dystrophy - Fujimoto, Sohya; Endo, Mako; Tonomura, Shigehito; Tsuji, Fuuga; Haraguchi, Hirotaka; Hasegawa, Kanna; Numao, Taisuke; Izumi, Ayaka; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Oyama, Yuki; et al. (Cells, 2025)
Fuchs endothelial corneal dystrophy (FECD) is a progressive disorder characterized by endothelial cell loss and excessive extracellular matrix (ECM) accumulation leading to corneal dysfunction. Emricasan, a pan-caspase inhibitor, was investigated for its therapeutic potential in suppressing these pathological changes. Patient-derived FECD cells and stress-induced cell models were treated with emricasan to assess its effects on apoptosis and ECM production. Caspase-specific knockdown experiments were performed to identify key mediators. Col8a2Q455K/Q455K mice, model mice of early-onset FECD, received twice-daily administration of 0.1% emricasan eye drops from 8 to 28 weeks of age. Endothelial cell density, hexagonality, cell size variation, and guttae area were evaluated by contact specular microscopy, while transcriptomic changes were analyzed via RNA sequencing. Emricasan effectively reduced apoptosis and ECM production in vitro by selectively inhibiting caspase-7 without affecting canonical TGF-β signaling. In vivo, emricasan-treated mice exhibited significantly higher endothelial cell density, improved hexagonality, and reduced variation in cell size compared with controls. Transcriptome analysis revealed distinct gene expression changes in the corneal endothelium following emricasan treatment. These findings suggest that emricasan exerts dual protective effects by inhibiting caspase-7-mediated ECM accumulation and broadly suppressing apoptosis, highlighting its potential as a pharmacological therapy for FECD.
CRIS-Team Scopus Importer:2025-04-25
Keywords: animal models; apoptosis; caspase inhibitor; corneal endothelial cells; extracellular matrix; Fuchs endothelial corneal dystrophy

The TCF4 Gene Regulates Apoptosis of Corneal Endothelial Cells in Fuchs Endothelial Corneal Dystrophy - Nakagawa, Tatsuya; Honda, Tetsuro; Yuasa, Taichi; Nishiuchi, Go; Sato, Masakazu; Tokunaga, Ayumi; Nakahara, Makiko; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Padmanabhan, Prema; Chatterjee, Amit; et al. (Investigative Ophthalmology & Visual Science, 2025)
PURPOSE. Fuchs endothelial corneal dystrophy (FECD) is a progressive corneal disorder characterized by excessive extracellular matrix (ECM) accumulation and corneal endothelial cell death. CTG trinucleotide repeat expansion in the transcription factor 4 (TCF4) gene represents the most significant genetic risk factor. This study aimed to elucidate the role of TCF4 in FECD pathogenesis through comprehensive proteomic analysis. METHODS. Corneal endothelial cells isolated from patients with FECD harboring TCF4 trinucleotide repeat expansion were immortalized to establish an FECD cell model (iFECD). CRISPR/Cas9-mediated genome editing was employed to generate TCF4-knockout iFECD cells. Whole-cell proteome analysis was performed using liquid chromatography–mass spectrometry, followed by pathway enrichment analysis of differentially expressed proteins (DEPs). The effects of TCF4 deletion on TGF-β–mediated protein aggregation and cell death were evaluated using Western blot analysis, flow cytometry, and aggresome detection assays. RESULTS. Proteomic analysis identified 88 DEPs among 6510 detected proteins. Pathway analysis revealed significant enrichment in ECM-associated pathways, oxidative stress responses, and cellular motility. TCF4 deletion attenuated TGF-β–induced cell death in iFECD cells. Concordantly, Western blot analysis demonstrated that TCF4 deletion suppressed TGF-β2–mediated cleavage of caspase-3 and poly (ADP-ribose) polymerase. Flow cytometric analysis of Annexin V–positive cells confirmed reduced apoptosis in TCF4-deleted cells following TGF-β2 treatment. Additionally, aggresome detection assays revealed that TCF4 deletion diminished TGF-β2–induced protein aggregation. CONCLUSIONS. This study demonstrates a crucial role for TCF4 in FECD pathogenesis, particularly in ECM regulation and protein aggregation–induced cell death.
CRIS-Team Scopus Importer:2025-03-28
Keywords: corneal endothelial cells; fuchs endothelial corneal dystrophy; TCF4

Transcriptional Profiling of Patients with Fuchs Endothelial Corneal Dystrophy with and Without Trinucleotide Repeat Expansion in TCF4 - Nakagawa, Tatsuya; Tokuda, Yuichi; Nakano, Masakazu; Tateishi, Ayana; Yasunaga, Mari; Tourtas, Theofilos; Schlötzer-Schrehardt, Ursula; Kruse, Friedrich; Tashiro, Kei; Koizumi, Noriko; Okumura, Naoki (Cornea, 2025)
Purpose:To investigate transcriptomic differences between patients with Fuchs endothelial corneal dystrophy (FECD) with and without trinucleotide repeat (TNR) expansion in the transcription factor 4 gene, as the genetic basis for patients with FECD lacking TNR expansion remains unclear.Methods:Bulk RNA sequencing was performed on corneal endothelial cells from 17 subjects: 10 patients with FECD [4 with repeat expansion lengths <50 (RE-) and 6 with expansions of 50 or more (RE+)] and 7 controls. Differential gene expression analysis was conducted using DESeq2. Principal component analysis (PCA), correlation matrix analysis, and heatmap visualization were used to evaluate gene expression patterns. Gene Ontology enrichment analysis was performed on differentially expressed genes (DEGs).Results:Analysis identified 509 DEGs (281 upregulated, 228 downregulated) between RE- and controls, and 640 DEGs (292 upregulated, 348 downregulated) between RE+ and controls. PCA revealed distinct gene expression patterns in both RE- and RE+ groups compared with controls. Between RE- and RE+ groups, only 10 DEGs were identified: ALDH3A1, ENSG00000286252, RNU6-645P, SNORD113-7, RNU6-429P, SNORA16A, COCH, EGFL6, SEMA3E, and ENSG00000228463. PCA, correlation matrix analysis, and heatmap visualization demonstrated high similarity in overall gene expression patterns between RE- and RE+ groups.Conclusions:Contrary to expectations, gene expression profiles showed remarkable similarity between patients with FECD with and without TNR expansion. Further investigation of the identified DEGs may provide insights into the role of TNR expansion in FECD pathophysiology.
CRIS-Team Scopus Importer:2025-03-28
Keywords: corneal endothelial cell; Fuchs endothelial corneal dystrophy; RNA sequencing; TCF4